Perspektif Mahasiswa Akuntansi Mengenai Faktor Yang Mempengaruhi Minat Dalam Pemilihan Karir Sebagai Akuntan Publik - Anandita; Adilla Putri Hardiyanto; Ningrum Pramudiati (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to examine social values, professional training, work environment, and level of religiosity on the interest of accounting students based on their perspective in choosing a career as a public accountant. Based on previous research, it still shows inconsistent results, so researchers are interested in re-examining it by adding a new variable that has never been studied before, namely the level of religiosity variable. The method used is a survey using a questionnaire. The technique of determining the sample is using purposive sampling. Multiple linear analysis technique using SPSS version 25. The sample of this research is 105 accounting students from PGRI Yogyakarta University or Yogyakarta State University. This study shows that social values, professional training, work environment, and level of religiosity have a positive effect on the interest of accounting students in choosing a career as a public accountant.